The Promotion of Student-Centered Learning Management of School Administrators in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2 - Sa-u, Hamdan (Al-HIKMAH Journal, 2022)
This research has the following objectives: 1) to study the level of promoting student-centered learning management of school administrators in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2. 2) to compare the level of promoting student-centered learning management of school administrators according to the viewpoints of school teachers in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2, classified by variables including gender, work experience and sizes of educational institution. 3) to compile recommendations on the promotion of student-centered learning management of school administrators according to the viewpoints of school teachers in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2. The sample group consisted of 144 school teachers in Sukhirin District selected by simple random sampling using the Krejcie & Morgan Table. The research tool was a questionnaire divided into three sections. The statistics used were frequency, percentage, arithmetic mean, standard deviation, t-test and F-test. Any difference found was tested by using the Scheffe's method. The results of the research indicated as follows. The overall level of promotion of student-centered learning management of school administrators in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2 was at a high level. Comparing the overall level of promotion of student-centered learning management of school administrators in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2, overall classified by gender and each aspect were indifferent and classified by work experience were overall indifferent. Considering each aspect, the only difference in each aspect was the management of learning resources with a statistical significance level of 0.01, overall classified by school size with a statistically significant difference at the level of 0.01. Consider each aspect, there was the only one aspect that was indifferent, which was classroom research. Suggestions on the promotion of student-centered learning management of school administrators in Sukhirin District under the Narathiwat Primary Educational Service Area Office 2 were as follows: School administrators should regularly monitor and evaluate the use of educational institutions' curriculums in order to improve and develop the curriculums to be up-to-date to keep up with the changes in the modern world society. Moreover, students should be encouraged to participate in the assessment of their own learning so that they could perceive strengths and weaknesses that are required to be developed. In addition, executives should have an exchange of opinions between supervisors and subordinates in order to exchange knowledge to build understanding and develop further teaching techniques that lead to the innovation development in the future onwards.